STUDY OF WEIGHT AND THE RELATIVE WEIGHT FOR SOME CUTS AND INTERNAL ORGANS AT DIFFRERENT AGES FOR FEMALES BROILER ROSS 308 - Razooqi , Ali Jawad (Diyala Agricultural Sciences Journal, 2015)
This research was carried out at the College of Agriculture - Diyala University during the period 02.07.2013 to 03.15.2013 with 60 of female broiler descended from the strain Ross 308، randomly selected and fed ad. libitum during periods starter ( 1-22 days )and growth (23 - 35 days) . Were slaughtered 20 females at every age of ages included in the study 25، 30، 35 days for the purpose of studying the effect of age on live body weight ، carcass weight gutted interior ، dressing percentage ، measure the length of the intestines ، weight and relative weight of the thighs ، breast ، wings ، liver ، heart ، gizzard ، pancreas and spleen. The birds were obtained from one of the fields civil in the area of Canaan – Diyala province . Measurements were carried out for the recipes studied results showed the following: 1- There is increasing highly significant ( p <0.01) in body weight (g) ، carcass weight gutted interior (g) ، the length of the intestine (cm) and a significant increase ( p <0.05) in liver weight (g)، the weight of the heart (g)، the weight of the pancreas (g)، spleen weight (g)، the weight of the thighs (g)، the weight of the breast (g)، the weight of the wings (g) and dressing percentage (%) of birds with age. In spite of the increase gizzard weight with age، but the differences were not significant. 2- The presence of decreasing highly significant( p <0.01) in the relative weight of the heart at the age of 35 days compared to the age of 25 and 30 days ، relative weight of the pancreas at the age of 35 days compared to the age of 25 days and relative weight of the gizzard with progress of the age of the bird. 3 - Age has no significant effect on the relative weight of the wings، thighs، breast and spleen . We conclude from this study that the increased weight of the bird with age increase carcass weight، dressing percentage، the length of the intestines، the weights of cuts (thighs، breast ، wings) ، the weights of Internal organs (liver ، heart، gizzard، pancreas، spleen) and reduce the relative weight of the heart ، gizzard and pancreas.